A comprehensive review of techniques in producing superhydrophobic surfaces on wood materials - Nazirah, Awang Husain; Nurul Huda, Abu Bakar; Rasidi, Roslan; Siti Noorbaini, Saimin; Mohamad Haafiz, Mohamad Kassim; Nurjannah, Salim (IPMEDIA SDN BHD, 2025)
The development of superhydrophobic wood surfaces has gained considerable interest in both industry and research, particularly due to its potential applications in wood-based products such as wood carvings, interior decorations, pavilions, wooden bridges, and pavements. Numerous studies have been conducted on fabrication theory models such as Young’s model, Wenzel model, and Cassie-Baxter model and various methods for creating superhydrophobic wood surfaces, such as sol-gel process, hydrothermal synthesis, coating with nanoparticle composites, and solution-immersion process. This paper aims to analyze the different techniques for producing superhydrophobic wood. Historically, the coatings and materials used to produce superhydrophobic wood surfaces were unsatisfactory due to the high cost of wood products or the insufficient strength of the wood. This paper will examine the most efficient techniques for manufacturing superhydrophobic wooden products that demonstrate not only superior functionality but also desirable attributes such as cost-effectiveness, exceptional durability, adequate air permeability, low bio-toxicity, high safety, and effective moisture management in heavily utilized wooden products.